Analysis of Students' Metacognition Skills in Solving Static Fluid Problems - Seska Malawau (Postgraduate, University of Mataram, 2023)
Students' errors in solving problems are caused by a lack of accuracy and calculation as well as the use of strategies in problem solving. So, to improve academic achievement, students need metacognitive skills so they can manage their cognition and find weaknesses so they can be corrected. This research aims to describe students' metacognitive skills in solving static fluid physics problems. The type of research used is quantitative descriptive research. Participants in this research were class XI science students at SMA Negeri 12 Ambon, a total of 26 students. The sample was selected using a purposive sampling technique. The instruments used are tests and non-tests in the form of essay test questions and the MAI metacognitive skills questionnaire. Based on the research results, it can be concluded that with a total of 26 students with metacognitive skills in planning and monitoring indicators in solving test questions, it can be seen that 21 students (80.8%) and 18 students (69.2%) have very good qualifications. Meanwhile, in the evaluation category, only 9 students (34.6%) qualified as very good. In this way, MAI can be used by teachers in solving students' physics problems. Therefore, students are expected to be more active and study hard, especially practicing solving physics problems with different problems in order to achieve good metacognitive skills